ANALISIS PENERAPAN MODEL PROBLEM-BASED LEARNING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMA: Model Problem-Based Learning, Kemampuan Berpikir Kritis Matematis, dan Systematic Literature Review - Anggiana, Agus Dede; Vici Suciwati; Diningrum, Rucita Iga (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Mathematical critical thinking skills are very important because the habit of critical thinking is needed in learning, it is hoped that students will become critical individuals. This study aims to analyze research related to the application of the Problem-Based Learning model to improve the mathematical critical thinking skills of high school student. This research uses the Systematic Literature Review (SLR) method, with this method the researcher reviews and identifies journals in a structured manner in which each process follows predetermined steps. In the identification stage, 16 journal articles were found based on the results of a literature search through the Google Scholar, SINTA, Scopus, and IOP science databases. In terms of the years of publication of articles on students mathematical critical thinking skills and the Problem-Based Learning model, the time range from 2019-2023 was selected. The results of this Systematic Literature Review (SLR) show that the research is dominated by the successful application of the Problem-Based Learning model in improving the mathematical critical thinking skills of high school students.